A. H. Sommerstein (ed.), Aeschylus. Oresteia. Agamemnon, Libation – Bearers, Eumenides. Edited and Translated by A. H. S., Cambridge, Mass. – London: Harvard University Press, 2008, pp. xxxviii+ 494, ISBN 978-0-674-99628-1. - BELLONI, LUIGI (Exemplaria Classica, 2012)
A. H. Sommerstein (ed.), Aeschylus, Fragments. Edited and Translated by A. H. Sommerstein, Cambridge, Mass. – London: Harvard University Press, 2008, pp. xiv + 363, ISBN 978-0-674-99629